6.9k views
12 votes
(6x −9)3−1=((6x−9)3)(0) Solve for X

User KentZhou
by
5.6k points

1 Answer

3 votes

Answer:

Explanation:

Remark

Anything multiplied by 0 = 0. So the whole right side is 0.

(6x - 9)*3 - 1 = 0 Add 1 to both sides.

(6x - 9)*3 - 1 + 1 = 0 + 1 Combine

(6x - 9)*3 = 1 Divide both sides by 3

(6x - 9)*3/3 = 1/3 Simplify

(6x - 9) = 1/3 Remove brackets. Add 9 to both sides

6x - 9+9 = 9 1/3 Combine

6x = 9 1/3

6x = 28/3 Divide both sides by 6

6x / 6 = 28/3 // 6 Invert the 6 and multiply.

x = 28/3 * 1/6

x = 28/18

Answer

x = 14/9

User Roman Slyepko
by
5.6k points